Physical rehabilitation of the painful shoulder - Quispe Rodríguez, Vladimir (2021)
The shoulder becomes one of the joints with the greatest mobility in the body, which is why it is considered the most unstable, the fact of being mobile and unstable implies that it suffers injuries due to inflammation of the connective tissue that covers the entire joint. causing pain and stiffness, this can originate in structures of the shoulder or away from it. The purpose of this review is to analyze, update and report on the physical rehabilitation of the shoulder and its functional process. The methodology. A meta revision was carried out in the database Scielo, Academic Google and PubMed, since articles were taken from the selection criteria published in Spanish, English and Portuguese. Results. In the presence of injuries to the shoulder because it is the most mobile joint, different physiotherapeutic interventions are used such as joint rest, cryotherapy, thermotherapy, massages, kinesitherapy, etc. in order to fully reset the shoulder. Conclusion. Physiotherapeutic interventions help a little to relieve shoulder pain; as well as, to be able to recover the function of this member.